Responding to Key Well-being Challenges in Austria - Gönenç, Rauf (OECD Publishing, 2013)
Important challenges for the future of Austrian well-being arise from demographic and environmental trends. The ageing of the population calls for a fair balance between life-time pension contributions and entitlements, drawing on the recent pension reform. Such progress will allow Austrians to make more informed choices between the length of their work and contribution periods and retirement length and income according to their preferences, without threatening fiscal sustainability. With female labour force participation rising, family policies should help reconcile equality of opportunity within families by promoting the availability, affordability and quality of support services. A growing share of immigrant groups with low human capital calls for remedial policies to preserve social cohesion. Environmental pressures arise from urban sprawl and the strong expansion of road transport. Turning around these trends will require more appropriate pricing of the externalities and better regional development policies to foster denser settlements that are well connected to public transport. This entails a need to strengthen coordination between different government layers and better integration of regional development with transport and housing policies. This Working Paper relates to the 2013 OECD Economic Survey of Austria (http://www.oecd.org/eco/surveys/austria-2013.htm)
Keywords: Social Issues/Migration/Health; Economics; Austria